Perichondrium - An Autologous Substitute for Temporalis Fascia in Type I Tympanoplasty: A Comparative Study - Bahnisikha Kayet; Aryabrata Dubey (Bengal Journal of Otolaryngology and Head Neck Surgery, 2019)
Introduction